Efficiency of Islamic Banks in Indonesia: Data Envelopment Analysis - Farandy, Alan Ray; Suwito, Demas Asfario; Dabutar, Lila Kondi (International Journal of Economics, Management and Accounting, 2017)
This paper measures the efficiency of Islamic commercial banks in Indonesia by analyzing factors that affect the level of efficiency using the two-stage data envelopment analysis (DEA) method. The objects of this study are 10 Islamic commercial banks in Indonesia which are analyzed from 2011 to 2014. Two methods are used in this study, namely nonparametric method of DEA in the first stage and Tobit model in the second stage. The actual average efficiency of Islamic commercial banks in Indonesia is at fairly good level with an average score 91.82, which means that although relatively inefficient, Islamic commercial banks in Indonesia are able to optimize their resource inputs to produce outputs as an intermediary institution. The application of the Tobit model uses asset (ASSET), non-performing financing (NPF), capital adequacy ratio (CAR), number of bank branches (BRANCH) and return on asset (ROA) as the explanatory variables. The results showed that the variables of assets, number of bank branches, and ROA significantly affect Islamic commercial bank efficiency, while CAR and NPF empirically do not have a significant effect on efficiency.